ANALISIS DALAM BERINTERAKSI PADA PEER TO PEER LENDING DALAM KREDIT MACET PINJAMAN ONLINE DAN PAYLATER YANG DIDOMINASI OLEH GENERASI Z - Kumalasari, Afiffah Layli; Lestari, Wuryaningsih Dwi (JURSIMA, 2022)
This research analyzes interactions on peer to peer lending platforms with a focus on bad credit online loans and paylater dominated by generation Z. Peer to peer lending has become an easy financing alternative in Indonesia that can be done digitally. However, the rapid growth of peer to peer lending also poses risks, including significant bad debts. This study aims to identify the development of peer to peer lending in Indonesia from 2020 to 2023 and examine the mitigation of bad credit risk in online loans and paylater that are widely used by generation Z. The research method used is qualitative with a descriptive method using a literature review approach, analyzing secondary data from various reliable sources such as OJK reports and journal articles. The research findings show that although peer to peer lending provides easy access to financing, many generation Zs are trapped in bad credit due to their inability to repay loans on time. This research provides recommendations for borrowers and lenders to be more careful in using peer to peer lending services that are legal and supervised by OJK to reduce the risk of bad credit.